Health, social and legal supports for migrant agricultural workers in France, Italy, Spain, Germany, Canada, Australia and New Zealand: a scoping review - Caxaj, C. Susana; Shkopi, Eriselda; Naranjo, Carmen T.; Chew, Alexa; Hao, Yi Ting; Nguyen, Michelle (Frontiers in Public Health, 2023)
Introduction We carried out a scoping review to examine what previous literature can teach us about practices and possibilities for support services for migrant agricultural workers. Methods Following guidelines for scoping reviews as outlined by Arksey and O’Malley (2005) and further refined by Levac et. al (2010) we conducted searches of several databases and two additional searches to capture regions of focus and more current literature. We used a thematic analysis to generate our themes. Results Our analysis yielded four key themes: (1) political, economic and legal factors; (2) living and working conditions; (3) facilitators/barriers to navigating services and supports and; (4) potential and existing strategies for social support for migrant agricultural workers. The first two themes pointed more to structural and material conditions that both posed barriers for this population to access supports, but also illustrated vulnerabilities that pointed to the need for a variety of services and protections. Under the third, we highlighted the ways that the design of services and supports, or their degree of accessibility, could shape the level of help available to this population. Lastly, potential and existing strategies for social support discussed in the literature included an emphasis on mental health and wellbeing, occupational health and safety training and documentation, and policy reforms to secure the status and address the precarity of this workforce. Discussion While research on social support and service provision for migrant agricultural workers is still in its infancy, a strength of this body of work is its attention to macro-level issues that advocate for strategies that address root factors that shape this group’s health. Further research is required to expand our understanding of social support roles and possibilities across other domains and sectors for this population.